Toxic Effects of Organometallic Compounds towards Marine Biota - Pellerito, L.; Barbieri, R.; Di Stefano, R.; Scopelliti, M.; Pellerito, C.; Fiore, T.; Triolo, F. (2002)
Organometallic derivatives are compounds containing a direct σ or π carbon metal linkage. Furthermore, the concept of the metallic atom must be extended to all the elements that are less negative than the carbon atom. As a consequence, taking into account all elements that are less negative than carbon and the number of existing organic compounds, it is possible to synthesize millions of organometallic derivatives. Several of these are extensively used in organic syntheses; others may find application in agriculture and in many other fields as pesticides, fire retardants, wood preservatives, antifouling agents, etc. In general, the organic derivatives of the metals are more toxic than the parent inorganic metal, with the alkyl derivatives bearing greater toxicity than the aryl ones. Furthermore, the mechanism of toxicity depends on the co-ordination atoms present in the attached biological molecule.